2009
DOI: 10.1111/j.1601-5223.1979.tb01657.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization of nucleolar organizing regions in European hedgehogs (Insectivora, Mammalia)

Abstract: The chromosomes of twenty‐six Western European and two Eastern European hedgehogs were analyzed by a silver‐staining technique in combination with G‐banding. Some differences in the localization of Ag‐NORs were found between and within the species. No distinct secondary constriction was noticed in the hedgehog karyotypes. The NORs were all located terminally, usually close to large C‐heterochromatic blocks. NORs were present in 6 chromosome pairs, although in individual animals Ag‐NORs were found in 3–5 pairs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…Therefore, differentiation in number and localization of NORs are considered to be important in the evolution of species. Similar results have been reported for two European shrew species (OLERT and SCHMID 1978), the Western and Eastern hedgehog (MANDAHL 1979) and also for various inbred mouse strains . More recently, WINKING et al (1980) found a wide variation in the localization of NORs in feral mice within the genus Mus and Mus musculus subspecies.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Therefore, differentiation in number and localization of NORs are considered to be important in the evolution of species. Similar results have been reported for two European shrew species (OLERT and SCHMID 1978), the Western and Eastern hedgehog (MANDAHL 1979) and also for various inbred mouse strains . More recently, WINKING et al (1980) found a wide variation in the localization of NORs in feral mice within the genus Mus and Mus musculus subspecies.…”
Section: Discussionsupporting
confidence: 89%
“…Similar results are reported by MIKELsAAR et d. (1977) for man, where the average frequency of homozygously occurring N O R sites was 75 O/ O. Contrary data are given by MANDAHL (1979) for the hedgehog, having only the low number of 44 % stained NORs.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The interest in and research on the cytogenetic characteristics of hedgehog karyotypes date back to between the late 1960s and the 1980s (7, 10, 13). These studies concentrated on identifying individual karyotype traits, mainly in the northern white-breasted hedgehog as the species inhabiting Europe (12, 13) and native species found in different territories (2, 5, 14).…”
Section: Introductionmentioning
confidence: 99%
“…1) from Thailand are preliminary presented along with the chromosomal localizations of the nucleolar organizer regions (NORs). Several studies have demonstrated variations in the chromosomal localization of NORs, including those of vertebrates using silver staining (Ag-NOR banding technique), which provided useful information of karyotypic evolution (Volleth 1987, Ono and Obara 1994, Mandahl 1979, Winking et al 1980, Shida et al 1999. The number of Ag-NORs was influenced by the activity of rRNA transcription (Babu andVerma 1985, Ono andYoshida 1998).…”
mentioning
confidence: 99%